Archaeological Research at the Jewish Cemetery on Okopowa Street in Warsaw - Szymon Lenarczyk; Zofia Kowarska (Fasciculi Archaeologiae Historicae)
The paper presents preliminary results of the archaeological research conducted in quarter 1 at the Jewish Cemetery at 49/51 Okopowa Street in Wola in Warsaw in the years 2020-2021, which was carried out in accordance with the guidelines of the Rabbinical Commission for Jewish Cemeteries in Poland, as well as respect for tradition and halakhic law. The results of archaeological work contribute to a better understanding of the history of the entire Warsaw necropolis from the time of its foundation, with a particular emphasis on the late 19th and early 20th century, to the times of the battles fought at the necropolis during World War II.